Mediaciones del yo y monstruosidad: Sor Juana o el “fénix” barroco - Solodkow, David (Revista Chilena de Literatura, 2009)
The following article explores one of the most important texts of New Spain's Baroque titled"Respuesta a Sor Filotea", written by Sor Juan Inés de la Cruz. The main objective of the article is to analyze the ways in which female and Creole subjectivity are constructed in New Spain. At the same time, the article explores the discursive and rhetoric transactions involved in the construction of that subjectivity. The article also examines the relationships between power, knowledge and desire within the de colonial lettered city, and the discursive devices of control and resistance to colonial and religious power. The analysis of the text shows the existence of an heterogeneous and fragmentary subjectivity in constant negotiation and tension with the social discourses of that time.